2017
DOI: 10.1590/s1678-9946201759028
|View full text |Cite
|
Sign up to set email alerts
|

Association of outcomes with comprehension, adherence and behavioral characteristics of tuberculosis patients using fixed-dose combination therapy in Contagem, Minas Gerais, Brazil

Abstract: The present study aimed to assess the association of outcomes with comprehension, adherence and behavioral characteristics of tuberculosis (TB) patients using fixed-dose combination (FDC) therapy in the city of Contagem, MG, Brazil. This study used standardized questionnaires to collect data. Outcomes included cure in 77.2% (64/ 83), noncompliance with treatment in 20.4% (17/ 83), and absence of organ failure or death cases. The rate of adherence to treatment was high (71.1% - 59/ 83), while the level of compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
(17 reference statements)
4
10
0
4
Order By: Relevance
“…Pulmonary TB was predominant (60.6%), followed by extrapulmonary TB (28.9%). A similar result of 62.7% was observed in a study carried out in the city of Contagem, Minas Gerais State 20 . In a national-based study, a similar result was also observed, between 37% and 40% for extrapulmonary TB, and 59% and 62% for pulmonary TB 21 .…”
Section: Discussionsupporting
confidence: 83%
“…Pulmonary TB was predominant (60.6%), followed by extrapulmonary TB (28.9%). A similar result of 62.7% was observed in a study carried out in the city of Contagem, Minas Gerais State 20 . In a national-based study, a similar result was also observed, between 37% and 40% for extrapulmonary TB, and 59% and 62% for pulmonary TB 21 .…”
Section: Discussionsupporting
confidence: 83%
“…11,[14][15][16][17][18][19][20][21] Population sizes ranged from 83 to 2416 patients, with mean age varying between 32.7 and 61.2 years. 18,22,23 The number of males was higher than females in all but two studies. 14,19 Patients were mostly treated using a daily dosage of isoniazid, rifampicin, pyrazinamide and ethambutol.…”
Section: Study Characteristicsmentioning
confidence: 71%
“…Thus, this factor may ultimately undermine treatment success (Munro et al 2007, Arbex et al 2010. Several studies have demonstrated the need to monitor patients who consume alcohol (Campani et al 2011, Oliveira and Antunes 2012, Silveira et al 2012, Viegas et al 2017. This study included six alcoholic patients, but this characteristic did not influence treatment outcome because all patients were ultimately cured.…”
Section: Discussionmentioning
confidence: 99%